Complete Genome Sequence of the Fire Blight Pathogen Erwinia amylovora CFBP 1430 and Comparison to Other Erwinia spp. - Theo H. M. Smits; Fabio Rezzonico; Tim Kamber; Jochen Blom; Alexander Goesmann; Jürg E. Frey; Brion Duffy (Molecular Plant-Microbe Interactions, 2010)
Fire blight, caused by the enterobacterium Erwinia amylovora, is a devastating disease of rosaceous plants that has global economic importance for apple and pear production and trade. The complete genome of E. amylovora CFBP 1430 was sequenced, annotated, and compared with the genomes of other Erwinia spp. Several singleton and shared features of the E. amylovora CFBP 1430 genome were identified that offer a first view into evolutionary aspects within the genus Erwinia. Comparative genomics identified or clarified virulence and fitness determinants and secretion systems. Novel insights revealed in the genome of E. amylovora CFBP 1430 hold potential for exploitation to improve the design of more effective fire blight control strategies.